Prevalence of resistance mutations associated with integrase inhibitors in therapy-naive HIV-positive patients in Baoding, Hebei province, China - Fan, Weiguang; Wang, Xiaodong; Zhang, Yuchen; Meng, Juan; Su, Miaomiao; Yang, Xuegang; Shi, Haoxi; Shi, Penghui; Lu, Xinli (Frontiers in Genetics, 2022)
Antiretroviral therapy (ART) regimens containing integrase strand transfer inhibitors (INSTIs) are the recommended treatment for human immunodeficiency virus type 1 (HIV-1)-infected patients in the most recent guidelines in China. In this study, we investigated INSTI resistance mutations in newly diagnosed therapy-naive HIV-positive patients in Baoding City, Hebei Province (China) to provide guidance for implementing routine INSTI-associated HIV-1 genotypic resistance testing. Plasma samples were collected from HIV-1-infected patients without treatment at Baoding People’s Hospital from January 2020 to December 2021. The part of HIV-1 pol gene encoding integrase was amplified, sequenced, and analyzed for INSTI resistance. Clinical data including demographic data, CD4+ T cell counts, HIV-RNA loads, and resistance mutations were collected. Treatment-naïve HIV-1 patients (n=131) were enrolled. We identified ten genotypes, and the predominant genotype was CRF01_AE in 67 patients (51.15%), CRF07_ BC in 39 patients (29.77%), subtype B in 11 patients (8.40%), and other subtypes (CRF68_01B, 3.82%; CRF55_01B, 1.53%, CRF80_0107, 1.53%; URFs 1.53%; and CRF103_01B, CRF59_01B, and CRF65_cpx, 1.4% each). Four major (E138A, R263k, G140S and S147G) and three accessory (H51Y, Q146QL and S153F) INSTI-resistance mutations were observed (genotype CRF01_AE, three patients; genotype B, one patient; and genotype CRF07_BC, one patient), resulting in different degrees of resistance to the following five INSTIs: raltegravir, elvitegravir, dolutegravir, bictegravir, and cabotegravir. The overall resistance rate was 3.82% (5/131). All INSTI-resistant strains were cross-resistant. The primary INSTI drug resistance rate among newly diagnosed HIV-infected patients in Baoding was low, but monitoring and research on HIV INSTI resistance should be strengthened in Baoding because INSTI-based regimen prescriptions are anticipated to increase in the near future.